Dynamic criteria for evaluation of the resistance of lake ecosystems of Belarusian Poozerie to external impact - Sukhovilo, Nina Y.; Vlasov, Boris P.; Novik, Aliaksei A. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article describes the results of the investigation of influence of external and internal water exchange on the stability of lakes to external impact. The objects of the study are 24 reservoirs of the Belarusian Poozerie, differing in origin, morphometric parameters, temperature regime and degree of economic using. The calculation of the mixing and stratification was carried out using the online model Lake Analyzer. The determination of the regularities of changes in the characteristics studied was based on methods of mathematical statistics. In the course of the study, regularities for the changes in hydro and thermodynamic parameters were established, depending on the morphometry of their basins and weather conditions, and the features of their influence on the stability of lakes to the external load were considered. The analysis of the interconnections of the complex zonal and azonal, external and internal factors and their quantitative assessment made it possible to distinguish three groups of reservoirs in terms of their resistance to anthropogenic effects: stable, mediumstable and unstable. The results obtained can be used to manage water ecosystems and determine the permissible load on them.